Synthesis and characterization of visible-light-driven novel CuTa2O6 as a promising practical photocatalyst - Alageshwaramoorthy, Krishnaprasanth; Mannu, Pandian; Mahalingam, Seetha; Nga, Ta Thi Thuy; Chang, Han-Wei; Masuda, Yoshitake; Dong, Chung-Li (Frontiers in Chemistry, 2023)
In this work, the novel CuTa2O6 phase was successfully synthesized by the hydrothermal and followed by the calcination process. The X-ray diffraction pattern confirms the formation of different phases. At a low temperature, CuTa2O6 exhibits the orthorhombic phase, whereas, at a higher temperature, it underwent a phase transition to a cubic crystal structure. X-ray photoelectron spectroscopic results suggest the presence of all the elements (Cu, Ta, and O). The optical studies were carried out using a UV-Vis DRS spectrophotometer. FESEM images confirm the spherical-shaped particles for the sample annealed at a high temperature. The local atomic and electronic structures around Cu and the contribution of the Cu oxidation state in the CuTa2O6 system were determined by X-ray absorption spectroscopy. To investigate the effective usage of CuTa2O6 in treating wastewater, its photocatalytic activity was investigated by evaluating its use in the photodegradation of MO dye under visible light irradiation. Moreover, the prepared CuTa2O6 photocatalyst exhibits significant photocatalytic activity in the degradation of MO dye and shows excellent stability; it is therefore a promising material for potential use in a practical photocatalyst. The CuTa2O6 photocatalyst suggests an alternative avenue of research into effective photo-catalysts for solar hydrogen water splitting.